John H. Molyneux, Simonides. A historical Study, Wauconda, Bolchazy-Carducci, 1992, 375 pp ISBN 0-86516-223-9 (Minerva. Revista de Filología Clásica, 2019)
Reseña de John H. Molyneux, Simonides. A historical Study, Wauconda, Bolchazy-Carducci, 1992, 375 pp ISBN 0-86516-223-9